Spatial distribution of economic activities and internal economic integration in Romania - Yaskal, Ihor; Maha, Liviu-George; Yaskal (Petrashchak), Oksana (My University, 2018)
: This paper aims to consider two tendencies in economy simultaneously: internal integration within the country and localization of economic activities. Firstly, we examine the quantitative measurement of internal economic integration in Romania. Different methods of economic integration measuring have been developed over time, so we have defined and discussed three approaches. To estimate a level of internal integration the link between the region's share in the total output and production factors was estimated and the pattern of distribution of these shares among the regions of Romania was assessed. The calculations have underlined an increasing tendency to deepen the internal economic integration of the Romanian economy. Secondly, the analysis of spatial distribution of economic activity has demonstrated that the capital region Bucharest-Ilfov concentrates the biggest share of employment and production. This indicates that initially there were higher economic activities and a labor deficit has been created, which was later covered by moving employees from other regions. As a result, the capital region concentrates 14.35% of the civil economically active population and 26.78% of the regional gross domestic product in 2014. By computing the location coefficient, we have observed that the counties with the biggest shares in the total GDP are characterized by a higher level of specialization simultaneously in many sectors.
Keywords: production factor distribution; Kullback-Leibler divergence; internal economic integration; spatial distribution of economic activities; specialization; location quotient